Thermodynamic aspects of enhanced oil recovery with supercritical C02 - Zudkevitch, D.; Czerwienskin, G. J.; Wang, Y. Z. (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper investigates how theories and data on phase equilibria and volumetric and transport properties of mixtures can be applied to some mechanism that have been proposed in the literature to aspects of EOR with CO2. In this work, the multiple-variable approach for establishing t he equation parameters (temperature, fugacity and density dependence) which has been applied by Joffe, Schroeder and Zudkevitch (27) to the Redilch-Kwong (R-K) equation was extended and was also applied to the Peng-Robinsoo (P-R) equation and to establishing the interaction parameters.